2014
DOI: 10.1039/c3ob42039f
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted acid catalyzed intramolecular benzylic cyclizations of alkylpyridines

Abstract: Aldehyde and ketone electrophiles incorporated into the side chains of 2- and 4-alkylpyridines participate in intramolecular aldol-like condensations with pyridine benzylic carbons in the presence of Brønsted acid catalysts. Pyridines featuring β-ketoamide side chains undergo cyclization in the presence of 10 mol% TfOH to afford pyridyl-substituted hydroxy lactams in good yield. These products were found to be resistant to further dehydration under a variety of conditions, however treatment with thionyl chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…4 We have initiated studies examining the reactivity of 4substituted alkylidene dihydropyridines and have reported intramolecular aldol-like reactions with attached carbonyl electrophiles. 5 More recently, we have demonstrated the use of anhydrobases as alkene partners in intramolecular Mizoroki− Heck cyclizations (Scheme 1A). 6 During attempts to develop intermolecular versions of this reaction, we screened aryldiazonium salts as organic electrophiles with the expectation that the high reactivity of aryldiazonium cations in Pd-catalyzed couplings would facilitate the desired Heck−Matsuda reaction.…”
mentioning
confidence: 99%
“…4 We have initiated studies examining the reactivity of 4substituted alkylidene dihydropyridines and have reported intramolecular aldol-like reactions with attached carbonyl electrophiles. 5 More recently, we have demonstrated the use of anhydrobases as alkene partners in intramolecular Mizoroki− Heck cyclizations (Scheme 1A). 6 During attempts to develop intermolecular versions of this reaction, we screened aryldiazonium salts as organic electrophiles with the expectation that the high reactivity of aryldiazonium cations in Pd-catalyzed couplings would facilitate the desired Heck−Matsuda reaction.…”
mentioning
confidence: 99%
“…Pigge and co-workers treated 4-hydroxypyrrolidin-2ones with excess thionyl chloride in the presence of a base to generate γ-hydroxy-γ-butyrolactams. 102 Indeed, by taking advantage of the dehydration properties of SOCl 2 , the reaction first produces 1,5-dihydro-2H-pyrrol-2-one intermediate A. A further reaction of A with SOCl 2 in the pres-ence of base affords species B and/or C, which then undergoes a nucleophilic addition reaction with H 2 O to form the γ-hydroxy-γ-butyrolactam (Scheme 54).…”
Section: Dehydrative Oxidation Of 4-hydroxypyrrolidin-2-onesmentioning
confidence: 99%
“…[1] Salicylaldehyde has mainly been obtained through the Reimer-Tiemannr eaction; [2] however, the yield of salicylaldehyde obtained by this method is low,a nd it is difficult to recover and recycle the large quantity of chloroform used with phenol in this reaction. [1] Salicylaldehyde has mainly been obtained through the Reimer-Tiemannr eaction; [2] however, the yield of salicylaldehyde obtained by this method is low,a nd it is difficult to recover and recycle the large quantity of chloroform used with phenol in this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Salicylaldehydes and salicylketones are importanti ntermediates in the productiono fp erfumes,d yes, plastics, agricultural materials, and drugs such as aspirin. [1] Salicylaldehyde has mainly been obtained through the Reimer-Tiemannr eaction; [2] however, the yield of salicylaldehyde obtained by this method is low,a nd it is difficult to recover and recycle the large quantity of chloroform used with phenol in this reaction. [3] The construction of benzene rings from acyclicb uilding blocks is av ersatile approachf or the preparation of functionalized arenes, and various synthetic methods have been documented in the literature.…”
Section: Introductionmentioning
confidence: 99%